2022
DOI: 10.4178/epih.e2022041
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, hypertension, diabetes mellitus, and hypercholesterolemia in Korean adults before and during the COVID-19 pandemic: a special report of the 2020 Korea National Health and Nutrition Examination Survey

Abstract: OBJECTIVES We investigated trends in obesity, hypertension, diabetes, and hypercholesterolemia before and during the coronavirus disease 2019 (COVID-19) pandemic in the Korean adult population. METHODS Data from 60,098 participants in the Korea National Health and Nutritional Examination Survey between 2011 and 2020 aged ≥19 were used. The age-standardized prevalence and annual percent changes (APCs) were calculated for obesity (body mass index ≥25 kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
1
25
0
3
Order By: Relevance
“…Lifestyle changes since the COVID-19 lockdown have increased the prevalence of chronic disease as well as obesity [8,[18][19][20]. In a study conducted using Korea National…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle changes since the COVID-19 lockdown have increased the prevalence of chronic disease as well as obesity [8,[18][19][20]. In a study conducted using Korea National…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…Health and Nutrition Examination Survey (KNHANES) data, the prevalence of obesity, hypertension, diabetes, and hyperlipidemia increased by 6%p, 1.8%p, 1.9%p, and 2.8%p in men before and after the COVID-19 pandemic, respectively [18]. A study in Italy showed that the prevalence of obesity increased from 37.8% to 51.3% and that of metabolic syndrome increased from 14.9% to 27% after the initial outbreak of COVID-19 [8].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…Obesity is a major health issue that causes many complications, including mental illness, cardiovascular disease (CVD), metabolic syndrome, cancer, and even death [ 1 ]. According to a study comparing chronic disease prevalence before and after the coronavirus disease 2019 (COVID-19) pandemic using data from the 2011 to 2020 National Health and Nutrition Examination Survey (NHANES), the prevalence of obesity in 2017–2019 was 34.2%, and that in 2020 was 38.4%; an increase of 4.2% was observed in Korean adults [ 2 ]. In middle-aged men aged 50–59 years, the prevalence of obesity was 42.8% in 2017–2019 and 48.3% in 2020, an increase of 5.4% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study comparing chronic disease prevalence before and after the coronavirus disease 2019 (COVID-19) pandemic using data from the 2011 to 2020 National Health and Nutrition Examination Survey (NHANES), the prevalence of obesity in 2017–2019 was 34.2%, and that in 2020 was 38.4%; an increase of 4.2% was observed in Korean adults [ 2 ]. In middle-aged men aged 50–59 years, the prevalence of obesity was 42.8% in 2017–2019 and 48.3% in 2020, an increase of 5.4% [ 2 ]. In middle-aged women aged 50–59 years, the prevalence of obesity was 30.2% in 2017–2019 and 32.4% in 2020, an increase of 2.2% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypertension (HTN) and diabetes mellitus (DM) in Korea is steadily increasing. According to the results of the Korea National Health and Nutrition Examination Survey 2020, the prevalence of HTN and DM has increased to 22.9% and 10.7%, respectively, compared to those in 2019 [ 1 ]. Although the overall mortality rate of COVID-19 is low, it may adversely affect the prognosis of people with HTN and DM, which are both associated with disease severity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%